Transit commuting, the network accessibility effect, and the built environment in station areas across the United States. (December 2016) - Renne, John L.; Hamidi, Shima; Ewing, Reid
Abstract: This study examines how the network accessibility effect and the built environment have an impact on the mode share for transit commuting across transit stations. Data is examined from 4400 fixed-guideway transit stations across the United States. We use a multiple-level model to account for variables at both the regional level and the neighborhood level. This is one of the first studies to include a variable that measures the network accessibility of jobs and population within walking distance of the transit network. Significant variables in predicting the mode share for transit commuting at the neighborhood level include income, population and jobs intensity, nonwhite status, transit type, jobs–population balance, walkability, and transit service frequency. However, the strongest predictor was the regional network accessibility variable. The results of this study support policies that promote transit-oriented development (TOD) at both the neighborhood and regional scales. The findings of this study should guide planners and policymakers to encourage dense, mixed-use development with high-quality walking environments near transit stations to boost the mode share of transit commuting.